The Mathematical Problem-Solving Ability through the Search, Solve, Create and Share (SSCS) Learning Model - Tiara, Tiara; Sukestiyarno, Yohanes Leonardus; Mulyono, Mulyono (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aimed to see the effect of applying the SSCS learning model with the mind mapping method on students' mathematical problem-solving abilities based on students' mathematical resilience. This research is experimental research with an experimental factorial design. The population of this study were all students of class X State Vocational High School 1 Sinabang, Aceh Province. The sample was chosen using the primary random sampling method, specifically selecting class X-TBS with 30 students as the experimental group and class X-OTKP with 30 students as the control group.   The tool employed consists of a set of test questions designed to assess one's aptitude for solving mathematical problems and a questionnaire aimed at gauging one's level of resilience in mathematical pursuits.   The data were subjected to analysis using a two-way ANOVA test.   The research findings and data analysis indicate the following conclusions: (1) There are disparities in students' mathematical problem-solving skills between the experimental and control classes. (2) There are disparities in students' mathematical problem-solving skills between the experimental and control classes when considering their levels of mathematical resilience (high, medium, and low). (3) no interaction effect is observed between implementing the SSCS learning model with the mind mapping method and students' mathematical resilience in their problem-solving abilities in mathematics.